2017
DOI: 10.1111/crj.12669
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double‐blind controlled trial comparing three sedation regimens during flexible bronchoscopy: Dexmedetomidine, alfentanil and lidocaine

Abstract: Introduction: No standardized sedation protocol is available for flexible bronchoscopy (FB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
(38 reference statements)
0
28
1
1
Order By: Relevance
“… 29 In the study by Altermatt et al, the findings also demonstrate that IV lidocaine can reduce propofol requirements during surgical stimulation and further confirm that the propofol-sparing effects of IV lidocaine are not related to pharmacokinetic interactions between propofol and lidocaine. 30 Another possible explanation for this finding is that lidocaine does not cause respiratory inhibition and dilates bronchial smooth muscle, 31 33 thereby preventing airway reactivity on emergence in obese patients. Additionally, IV lidocaine could induce a stimulation of the ventilatory response to carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“… 29 In the study by Altermatt et al, the findings also demonstrate that IV lidocaine can reduce propofol requirements during surgical stimulation and further confirm that the propofol-sparing effects of IV lidocaine are not related to pharmacokinetic interactions between propofol and lidocaine. 30 Another possible explanation for this finding is that lidocaine does not cause respiratory inhibition and dilates bronchial smooth muscle, 31 33 thereby preventing airway reactivity on emergence in obese patients. Additionally, IV lidocaine could induce a stimulation of the ventilatory response to carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…Older studies comparing alfentanil and midazolam sedation have shown that alfentanil sedation results in less cough, but not necessarily less discomfort or improved ease of the procedure 21 22. The trial comparing alfentanil to placebo did not find a statistically significant difference in cough, and did not address subject discomfort 20. Sedation was not randomised in our study, but offered to all.…”
Section: Discussionmentioning
confidence: 68%
“…Bronchoscopy sedation with alfentanil has only recently been compared with placebo or dexmedetomidine in a relatively small randomised controlled trial. The authors reported more events of hypoxaemia and heart rate changes in the alfentanil group, but present few clinically significant differences between the groups 20. Older studies comparing alfentanil and midazolam sedation have shown that alfentanil sedation results in less cough, but not necessarily less discomfort or improved ease of the procedure 21 22.…”
Section: Discussionmentioning
confidence: 96%
“…These findings may be attributable to the ability of dexmedetomidine to selectively inhibit the activation of the central nervous system and peripheral a2 adrenergic receptors, which reduce sympathetic nerve activity and abnormally increase blood pressure and heart rate under stress to maintain hemodynamic stability. 15 Riachy et al 15 previously reported a comparison of dexmedetomidine with other sedation regimens and proposed a protocol as a first step towards standardizing sedation practices in flexible bronchoscopy, which may be adopted in further studies to optimize treatment strategies.…”
Section: Discussionmentioning
confidence: 99%